2023
DOI: 10.2196/44810
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Literature- and Subreddit-Derived Laboratory Values in Polycystic Ovary Syndrome (PCOS): Validation of Clinical Data Posted on PCOS Reddit Forums

Abstract: Background Polycystic ovary syndrome (PCOS) is a heterogeneous condition that affects 4% to 21% of people with ovaries. Inaccessibility or dissatisfaction with clinical treatment for PCOS has led to some individuals with the condition discussing their experiences in specialized web-based forums. Objective This study explores the feasibility of using such web-based forums for clinical research purposes by gathering and analyzing laboratory test results p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Lastly, we believe that studies of OHCs can help design interventions to improve care, as argued in previous studies [30,49,51,52].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Lastly, we believe that studies of OHCs can help design interventions to improve care, as argued in previous studies [30,49,51,52].…”
Section: Discussionmentioning
confidence: 71%
“…An existing study of a PCOS subreddit has also found concordance between the OHC user population and research-identified patient cohorts [51]. Although the PCOS OHC includes patients that are typically excluded from clinical trials (such as those with multiple conditions), trends found in laboratory test results posted to the community are consistent with clinically reported results.…”
Section: Rq1: What Aspects Of the Endometriosis Experience Are Discus...mentioning
confidence: 64%
See 1 more Smart Citation